Global Trends in Educational Program Evaluation: Bibliometric Analysis for Education Quality Improvement - Loso Judijanto; Heni Widyaningsih; Desty Endrawati Subroto; Muhammad Arsyad; Erik Novianto (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis to map global trends in educational program evaluation, focusing on research outputs, thematic evolution, and key scholarly networks from 2000 to 2024. Utilizing citation metrics, yearly publication graphs, and VOSviewer visualizations of keyword co-occurrences, the research identifies significant shifts in thematic focus, delineates interconnected research clusters, and highlights the influential contributions within the field. The analysis reveals a notable increase in publications related to educational evaluation during the early 2000s with a peak between 2010 and 2018, indicating heightened research interest coinciding with global educational reforms. Thematic clusters around